The pandemic changes daily life and ways of living: technosociality and user/families experiences - Leila Cristine do Nascimento; Tamires Carolina da Silva; Daniela Priscila Oliveira do Vale Tafner; Virgínia Junqueira Oliveira; Selma Maria da Fonseca Viegas (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: understand the changes imposed by the COVID-19 pandemic in the daily lives of users of Primary Health Care and their families and its impact on self-care and health promotion. Methods: this is a holistic-qualitative multiple case study, based on the Comprehensive Sociology of Everyday Life, in which 61 users participated. Results: experiencing a new daily life in COVID-19 pandemic times, users express their feelings, adaptation to new habits and ways of living. Health technologies and virtual social networks stand out in helping with everyday tasks, in communicating with loved ones and health professionals, and in validating dubious information. Faith and spirituality arise in the face of uncertainty and suffering. Final Considerations: it is imperative to pay close attention to the changes in daily life caused by the COVID-19 pandemic, in order to offer care directed to the singular and collective needs.